Breaking Stereotypes: Life and Works of Begum Rashid Jahan, Ismat Chugtai and Begum Khurshid Mirza - Sahira Abbasi (JSSH, 2024)
In the west, 19th century witnessed various social reform movements like movement against slavery, fight for public schools, humane prisons, greater political representation and the movement for women’s civil, political and economic rights. Indian society during 19th century was experiencing political transition and by becoming Britain’s colony India began to experience the impact of western ideas on its society as well. One such impact was that of feminism which demanded greater social, economic and political rights for women all over the world. Indian society was dominantly patriarchal in nature and so, these western ideals of women freedom and social equality were not very much welcomed among the masses of India. During the late 19th century and the early 20th century there were a few brave women who broke the customs, taboos and social stereotypes and set an example of courage and bravery.